Case Report: PANDAS and Persistent Lyme Disease With Neuropsychiatric Symptoms: Treatment, Resolution, and Recovery - Cross, Amy; Bouboulis, Denis; Shimasaki, Craig; Jones, Charles Ray (Frontiers in Psychiatry, 2021)
This case report describes the diagnosis and treatment of a pre-pubertal (onset at age 7) Caucasian female with serological evidence of Lyme disease accompanied by multiple neuropsychiatric symptoms six months following a vacation in a tick endemic area of the United States. The patient also met the clinical diagnostic criteria for PANDAS (Pediatric Autoimmune Neuropsychiatric Disorder Associated with Strep)1-2, with serological evidence of three distinct episodes of streptococcal pharyngitis. All three episodes of strep occurred during the six month interval between suspected Lyme disease exposure and the onset of multiple neuropsychiatric symptoms. Her sometimes incapacitating symptoms followed a relapsing and remitting course that impacted her personal, family, social and academic domains. Over a span of 31 consecutive months of treatment with various antimicrobials and 3 courses of intravenous immunoglobulins, she became symptom free and remains so at the time of this publication.